INOVASI INSINERATOR SEDERHANA UNTUK MENGURANGI PENUMPUKAN SAMPAH MASYARAKAT NAGARI KOTO GADANG ANAM KOTO: TINJAUAN LITERATUR - Athifa Asyari; Rayhan Pramana Septiawan; Mutiara Dwi Putri; Chairunisa Kamilah; Gunawan Pratama; Firman Wahyu Saputra; Miftahul Khair (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Residual-waste accumulation and open burning remain problems in areas with limited treatment services. This study reviews 26 sources to assess a simple incinerator concept for Nagari Koto Gadang Anam Koto. Nine studies with original input and residue data reported batch mass or volume reductions of 62.88% to 96.94%. A material-flow evaluation showed that incineration handled 25% to 30% of total waste input within an integrated system. Waste type, moisture, chamber loading, temperature, residence time, air supply, and flue-gas control affected residue and smoke. Smoke colour alone did not demonstrate emission safety. All numerical findings are secondary data, not local measurements. The concept requires waste sorting, trained operators, mass recording, and emission testing before field implementation.